2009
DOI: 10.1007/s00428-009-0858-z
|View full text |Cite
|
Sign up to set email alerts
|

Borderline and malignant phyllodes tumors display similar promoter methylation profiles

Abstract: Mammary phyllodes tumors (PTs) are uncommon fibroepithelial neoplasms. On the basis of histologic criteria, PTs can be divided into benign, borderline, and malignant groups; however, the histologic distinction of PTs is often difficult and arbitrary. In breast cancer, promoter hypermethylation is a common phenomenon, but there are no data available concerning methylation status in PTs. The aim of this study was to assess whether the methylation profiles support the classification of PTs into three subgroups. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 22 publications
1
11
0
Order By: Relevance
“…Therefore, although the frequency of CIMP-H in this study is lower than expected, it is in accordance with these larger European studies. More importantly, the poor prognostic effect observed here in patients with CIMP-H and CIMP-L tumors in comparison to those showing CIMP-negativity agrees with several works from other authors (Ward et al, 2003; Kim et al, 2009; Dahlin et al, 2010). In addition, our findings show no association of MGMT methylation with prognosis, a result which was also recently observed by Shima et al (2011).…”
Section: Discussionsupporting
confidence: 93%
“…Therefore, although the frequency of CIMP-H in this study is lower than expected, it is in accordance with these larger European studies. More importantly, the poor prognostic effect observed here in patients with CIMP-H and CIMP-L tumors in comparison to those showing CIMP-negativity agrees with several works from other authors (Ward et al, 2003; Kim et al, 2009; Dahlin et al, 2010). In addition, our findings show no association of MGMT methylation with prognosis, a result which was also recently observed by Shima et al (2011).…”
Section: Discussionsupporting
confidence: 93%
“…Moreover, GSTP1 hypermethylation and therefore gene silencing was associated to increased grades of mammary phyllodes tumors. As such GSTP1 methylation patterns allow distinguishing two groups: one benign unmethylated group as well as samples presenting hypermethylated GSTP1 gene promoters in the borderline/malignant tumor group (Kim et al, 2009). Recently, Miyake et al (2012) demonstrated that GSTP1 expression predicts poor pathological complete response to neoadjuvant chemotherapy in ER-negative breast cancer.…”
Section: Regulation Of Cellular Activities Through Epigenetic Mechanismsmentioning
confidence: 99%
“…Kim et al 41 studied hypermethylation via multiplex-nested PCR in 87 PTs and found a trend of increasing methylation with increasing grade, with a significant increase when borderline and malignant PTs were compared with benign PTs.…”
Section: Cytogenetic and Molecular Genetic Pathology Of Ptsmentioning
confidence: 99%